2019
DOI: 10.1126/sciadv.aau5106
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 specifies neural crest cell fates through pyruvate-alanine cycling

Abstract: Metabolic processes underlying the development of the neural crest, an embryonic population of multipotent migratory cells, are poorly understood. Here, we report that conditional ablation of the Lkb1 tumor suppressor kinase in mouse neural crest stem cells led to intestinal pseudo-obstruction and hind limb paralysis. This phenotype originated from a postnatal degeneration of the enteric nervous ganglia and from a defective differentiation of Schwann cells. Metabolomic profiling revealed that pyruvate-alanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 84 publications
3
37
0
Order By: Relevance
“…This result highlights the crucial role of gluconeogenesis deregulation in the development of the lethal phenotype in mutant mice. Interestingly, recent studies have identified transaminases as effectors of other metabolic functions of Lkb1 involved in the epigenetic reprogramming occurring during malignant transformation 44 , or during the glial fate specification of neural crest cells 45 . Together with our data, these results highlight a key unsuspected role of aminotransferases in Lkb1 function.…”
Section: Discussionmentioning
confidence: 99%
“…This result highlights the crucial role of gluconeogenesis deregulation in the development of the lethal phenotype in mutant mice. Interestingly, recent studies have identified transaminases as effectors of other metabolic functions of Lkb1 involved in the epigenetic reprogramming occurring during malignant transformation 44 , or during the glial fate specification of neural crest cells 45 . Together with our data, these results highlight a key unsuspected role of aminotransferases in Lkb1 function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of alanine has been highlighted in cancer [66]. Although there is no solid evidence of its role in promoting AML, it is supposed to act in tandem wilth the liver kinase LKB1 [69]. Leukemic stem cells (LSCs) are an essential area of research that has been discussed over the years with regard to AML [93].…”
Section: Discussionmentioning
confidence: 99%
“…However, the liver kinase B1 (LKB1) is an important -master kinase‖ of metabolism in various cancers, and is thought, for the most part, to act as a tumor suppressor in AML by downregulating the mTOR pathway and subsequently decreasing cell growth and survival [68]. Recently, it was found that LKB1 regulates ALT activity and thus the pyruvate-alanine conversion in neural crest cells, in a pathway that relies on mTOR [69]. As LKB1 is highly active under nutrient-deficient conditions in AML, it could potentially affect alanine metabolism by regulating ALT activity in a similar manner, although this premise remains hypothetical.…”
Section: Alanine Metabolism In Cancersmentioning
confidence: 99%
“…LKB1-deficient adult mice displayed exhaustion of the HSC pool. LKB1 is also involved in the regulation of stem cell fates, such as the induced pluripotent stem (iPS) cell-derived mesenchymal stem cells, neural crest cells, and intestinal stem cells [ [116] , [117] , [118] ]. It is believed that LKB1 plays an essential role in stem cell homeostasis.…”
Section: The Double-edged Sword Behavior Of Lkb1mentioning
confidence: 99%